The development of an experimental integrity instrument for various cultural groups as conceptualised form the South African personality inventory (SAPI) project - Lotter, Megon (Stellenbosch : University of Stellenbosch, 2011)
Thesis (MComm (Industrial Psychology))--University of Stellenbosch, 2011.